The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/are.14336
|View full text |Cite
|
Sign up to set email alerts
|

Growth‐promoting bacteria for the green seaweed Ulva clathrata

Abstract: Seaweed production represents one of the rising activities in the aquaculture industry. This study explores the impact of bacteria associated with the growth of Ulva clathrata, a promising alga in the field of food and bioremediation. Fifty‐six bacteria isolated from four seaweed (Caulerpa sp., Gracilaria sp., Ulva lactuca and U. clathrata) were tested to evaluate their effect on U. clathrata growth. Eight of them showed a significant growth‐promoting effect (p < .05). Isolates Ul‐11 and Ul‐12 from U. lactuca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…In the absence of these specific bacteria, Ulva merely grows as a loose aggregation of cells without rhizoids or proper cell wall development. In addition to morphogenesis, bacteria are known to promote Ulva growth (Gemin et al, 2019), induce settlement of zoospores (Joint et al, 2000; Patel et al, 2003) and affect the biochemical composition of the seaweed (Polikovsky et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of these specific bacteria, Ulva merely grows as a loose aggregation of cells without rhizoids or proper cell wall development. In addition to morphogenesis, bacteria are known to promote Ulva growth (Gemin et al, 2019), induce settlement of zoospores (Joint et al, 2000; Patel et al, 2003) and affect the biochemical composition of the seaweed (Polikovsky et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial communities are mainly composed of Alphaproteobacteria and Bacteroidete members, especially within the Rhodobacteriaceae , Sphingomonadaceae , Flavobacteriaceae, and Sapropiraceae families [ 212 ]. Several of these marine bacteria will have an impact on the morphologies and polymorphisms of various Ulva species, such as U. clathrata [ 213 ], U. fasciata [ 214 ], U. intestinalis [ 215 ], U. linza [ 216 ], U. mutabilis [ 215 , 217 ], or U. pertusa [ 218 ].…”
Section: Marine Macroalgaementioning
confidence: 99%
“…While studies have identified the bacteria required for Ulva development [ 1 , 150 , 151 ], studies identifying specific bacteria influencing the growth of mature thallus and the biochemical composition of the biomass are still lacking. To date, a limited number of studies have attempted to demonstrate that certain bacteria can promote Ulva growth [ 167 , 168 ] and can affect the biochemical composition of Ulva [ 116 ]. Further, examination of the molecular mechanisms driving Ulva : microbial interactions is still limited.…”
Section: Strategies To Improve Ulva Biomass Yield ...mentioning
confidence: 99%